Chitosan and HPMCAS double-coating as protective systems for alginate microparticles loaded with Ctx(Ile21)-Ha antimicrobial peptide to prevent intestinal infections - Roque-Borda, Cesar Augusto [UNESP]; Saraiva, Mauro de Mesquita Souza [UNESP]; Macedo Junior, Wagner Dias [UNESP]; Márquez Montesinos, José Carlos Estanislao; Meneguin, Andréia Bagliotti [UNESP]; Toledo Borges, Anna Beatriz [UNESP]; Crusca Junior, Edson [UNESP]; Garrido, Saulo Santesso [UNESP]; de Almeida, Adriana Maria [UNESP]; Marchetto, Reinaldo [UNESP]; Chorilli, Marlus [UNESP]; Berchieri Junior, Angelo [UNESP]; et al. (Elsevier, 2023)
The incorrect use of conventional drugs for both prevention and control of intestinal infections has contributed to a significant spread of bacterial resistance. In this way, studies that promote their replacement are a priority. In the last decade, the use of antimicrobial peptides (AMP), especially Ctx(Ile21)-Ha AMP, has gained strength, demonstrating efficient antimicrobial activity (AA) against pathogens, including multidrug-resistant bacteria. However, gastrointestinal degradation does not allow its direct oral application. In this research, double-coating systems using alginate microparticles loaded with Ctx(Ile21)-Ha peptide were designed, and in vitro release assays simulating the gastrointestinal tract were evaluated. Also, the AA against Salmonella spp. and Escherichia coli was examined. The results showed the physicochemical stability of Ctx(Ile21)-Ha peptide in the system and its potent antimicrobial activity. In addition, the combination of HPMCAS and chitosan as a gastric protection system can be promising for peptide carriers or other low pH-sensitive molecules, adequately released in the intestine. In conclusion, the coated systems employed in this study can improve the formulation of new foods or biopharmaceutical products for specific application against intestinal pathogens in animal production or, possibly, in the near future, in human health.
Keywords: AMP; Chitosan; Enteric coating; HPMCAS; In vitro release; Microparticles